NADPH from the oxidative pentose phosphate pathway drives the operation of cyclic electron flow around photosystem I in high‐intertidal macroalgae under severe salt stress. Issue 4 (6th October 2015) - Lu, Xiaoping; Huan, Li; Gao, Shan; He, Linwen; Wang, Guangce
Abstract : Pyropia yezoensis (Bangiales, Rhodophyta) is a representative species of high‐intertidal macroalgae, whose blades can tolerate extreme stresses, such as salt stress and desiccation. In this study, the photosystem (PS) responses of P. yezoensis blades under salt stress were studied. Our results showed that when the effective photochemical quantum yield of PS (Y) II decreased to almost zero under high salt stress, YI still had a relatively high activity rate. PSII was therefore more sensitive to salt stress than PSI. Furthermore, in the presence of 3‐(3′, 4′‐dichlorophenyl)‐1, 1‐dimethylurea (DCMU), YI rose as salinity increased. The YI values for DCMU‐treated thalli decreased in the presence of glucose‐6‐phosphate dehydrogenase (EC 1.1.1.49, G6PDH) inhibitor (glucosamine, Glucm). The YI values were ∼0.09 in the presence of methyl viologen (MV) and almost zero in the presence of dibromothymoquinone (DBMIB). These results demonstrated that under severe salt stress (120‰ salinity) PSI activity was driven from a source other than PSII, and that stromal reductants probably supported the operation of PSI. Under salt stress, the starch content decreased and soluble sugar levels increased. The G6PDH and 6‐phosphogluconate dehydrogenase (EC 1.1.1.44) activities increased, but cytosolic glyceraldehyde 3‐phosphate dehydrogenase (EC 1.2.1.12) activity decreased. Furthermore, the NADPH content increased, but NADH decreased, which suggested that soluble sugar entered the oxidative pentose phosphate pathway (OPPP). All these results suggested that NADPH from OPPP increases the cyclic electron flow around PSI in high‐intertidal macroalgae under severe salt stress.